The Effect of Reminiscence Therapy for Elderly Depression in BPPLU of Bengkulu - Dian Dwiana Maydinar; S. Effendi; Afifa Tusholehah (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
Depression in the elderly if not immediately dealt with quickly can cause brain shrinkage, so that the elderly will experience a decrease in quality of life, decreased social and physical function, disability, suicide risk and increased mortality in the elderly. This study aimed to determine the effect of reminscene group therapy on depression in the elderly at BPPLU Kota Bengkulu. This study used a pre-experimental one group pre test and post test design. The population in this study were 60 elderly at the BPPLU in Bengkulu City. The sampling technique used Purposive Sampling techniques as many as 14 elderly. The data used are primary data and secondary data. Data were analyzed using univariate and bivariate analysis with Shapiro Wilk data normality test and Paired T test. The results showed that the average depression before reminiscene therapy was 8.21 with a standard deviation of 1.626, the average value of depression after reminiscene therapy was 6.71 with a standard deviation of 2.234, there was an effect of reminiscene group therapy on depression in the BPPLU city Bengkulu. It is expected that health workers can routinely carry out group therapy in treating depression in the elderly. Keywords: depression, elderly, reminiscene group therapy